Constitutional protection for woman against inequality in Malaysia: Beatrice's case and the emerging issues/Obstacles in view of globalization - Mokhtar, Khairil Azmin (Jabatan Undang-Undang, Universiti Teknologi MARA Johor, Segamat, Johor Darul Takzim, 2006)
In the era of globalization and privatization the private sector plays very significant role in the economy_ Naturally the employment sector is dominated by private enterprises and the main employer shall be the private sector. Although significant measures have been taken by the Malaysian authorities in order to protect the rights of female employee, there still a lot of room for improvement. This writing intends to observe the legal and constitutional framework for the right of equal treatment of female employee. Later the discussion is focused on the effect of the recent decision of the Federal Court in Beatrice v. Sistem Penerbangan Malaysia & Anor 1 on the right of woman in relation to employment.